CAMPS, A.: CRÓNICAS, COMENTARIOS Y NOTICIAS DE TEMÁTICA ITALIANA EN ‘LA VANGUARDIA ESPAÑOLA’ (1945-1962) - Assumpta Camps (Transfer, 2012)
In this essay, conceived as continuation of our previous works on the topic, we will focus on the study of the news and comments on Italy and the Italian literature published in the Spanish press between 1945 and 1962 (year commonly considered as the beginning of a new period in the cultural history of Franco’s regime). For that reason, we will analyze any Italian reference that appear in one of the most important Spanish newspapers of that time, La Vanguardia, by then, called La Vanguardia Española, following the spirit of the time.